Processo de extração de DNA humano contaminado com solo - Faro, Cynthia Cristina Pagliari de (2012)
The index of crime in our society grows to each day. It is observed, in special the increase of homicides, practiced in lands or small farms, where the briefing of the authorship of the criminal act is not had. The difficulty of criminal identification inhabits in the fact of the biological residues found in these places to be in contact with the ground of different natures. The importance of this work is in the possibility to present a reply to the society concerning the identification human being from contaminated biological vestiges of blood with ground. The objective of this work is to develop a protocol of extraction of DNA capable to isolate the human DNA of the constituent of the ground with intention to identify the possibly involved individual in criminal act. For four protocols of extraction of DNA they had been in such a way used, being two conventional protocols and two new protocols, developed for our team. 720 contaminated samples of blood with ground, being 240 for each type of ground had been used. 3 different types of ground had been used (wasteland, sand of the beach and mangrove). Of the 240 contaminated samples of human blood with ground, 120 had been submitted to the extraction of the DNA immediately after the contact with the ground (Time 0) and 120 submitted samples the extraction of DNA after a passed time of 72 hours of the contact with the ground (Time 72). The results had shown that the extracted samples of human blood in Time 0 for the conventional protocols had only amplified for one of the types of ground whereas the new protocols had gotten a good amplification for the three tested types of ground. Already for the effected Human extraction of DNA in Time 72 the amplification of the samples extracted with the conventional protocols was not observed. The new protocols had only provided to amplification and consequence identification human being. One concluded that the two new protocols, developed for our team, had presented resulted superior comparative to the too much protocols of extraction of DNA for the 3 types of tested ground, thus being able, to assist in the briefing of crimes and to provide to more sensitivity the usual techniques.